Indonesian aquaculture futures – Evaluating environmental and socioeconomic potentials and limitations. (20th September 2017) - Henriksson, Patrik John Gustav; Tran, Nhuong; Mohan, Chadag Vishnumurthy; Chan, Chin Yee; Rodriguez, U-Primo; Suri, Sharon; Mateos, Lara Dominguez; Utomo, Nur Bambang Priyo; Hall, Stephen; Phillips, Michael John
Abstract: Indonesia is the world's second largest seafood producer, but capture fisheries landings have stagnated over the last decade. In response, the Indonesian government has set ambitious targets for expanding the aquaculture sector up to 2030. The present research therefore quantifies environmental impacts using life cycle assessments (LCAs), and some socioeconomic indicators, for six alternative scenarios projecting the growth of Indonesia's aquaculture up to 2030 by Tran et al. (2017). From these results, policy implications are drawn and suggestions for improvements made for gearing the Indonesian government and seafood industry towards blue growth. Ten dominant aquaculture farming systems were characterized and benchmarked using LCA, building upon data collected on Sumatra, Java, Lombok, and Sulawesi between 2014 and 2015. Assuming business as usual up to 2030, the impacts/indicators global warming (3.3-fold increase), acidification (3.3-fold increase), eutrophication (3.5-fold increase), land-use (3.6-fold increase), freshwater consumption (4-fold increase), energy use (3.4-fold increase), reliance on wild fish (3.4-fold increase), total fish output (3.3-fold increase), and full-time employments (3.3-fold increase) would increase by three to four-fold, while monetary value would increase almost six-fold. Business as usual alongside several other future scenarios would consequently require more wild fish and land than is physically manageable using current production practices, while still not satisfying the growth targets set by the Indonesian government. A major transformation of the aquaculture industry supported by public policies is therefore needed to avoid extensive environmental damage. Similar studies on future food growth projections are encouraged in order to give more realistic recommendations to policy makers. Graphical abstract: Highlights: LCAs were carried out for ten Indonesian aquaculture systems. Environmental and socio-economic indicators were evaluated up to 2030. Grouper and Asian tiger shrimp had the largest environmental impacts. Clarias and Pangasius catfishes had the lower impacts, but also monetary value. Resource limitations will likely limit Indonesian aquaculture growth before 2030.